2022
DOI: 10.23880/phij-16000235
|View full text |Cite
|
Sign up to set email alerts
|

Transformational Leadership’s Influence on Teacher Well-Being in International Schools

Abstract: Teachers working and living in foreign countries often rely upon the international school community to offer the support and stability customarily provided by their home environments. This study explores the influence of leadership philosophy on teacher well-being and describes the transformational leadership behaviors that support a healthy school climate. By developing the skills and behaviors identified in this study, transformational leaders in international schools can decrease teacher stress and increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In addition, Windlinger (2021) found that school leadership is associated with different types of teacher well‐being (e.g., leading to a positive impact on the work engagement of teachers). More relevant to this study, Matthew and Adam (2022) found that transformational leadership of school leaders affected teachers' workload stress and well‐being in international schools in Thailand. Further, the effects of workload stress have focused on teachers' mental health and job satisfaction.…”
Section: Conceptual Frameworkmentioning
confidence: 86%
“…In addition, Windlinger (2021) found that school leadership is associated with different types of teacher well‐being (e.g., leading to a positive impact on the work engagement of teachers). More relevant to this study, Matthew and Adam (2022) found that transformational leadership of school leaders affected teachers' workload stress and well‐being in international schools in Thailand. Further, the effects of workload stress have focused on teachers' mental health and job satisfaction.…”
Section: Conceptual Frameworkmentioning
confidence: 86%